(untitled) (Innovaciones Educativas, 2023)
This article emerges from an equity approach based on the research Socio-educational factors and inclusion-exclusion dynamics in the Secondary Education programs of the Ministry of Public Education. It seeks to investigate the genesis and evolution of educational modalities and programs to know the why and wherefore as well as the conditions that led to its origin. This contribution shows the diversity of educational options that make up the network of institutions that are part of public secondary education in Costa Rica, as well as the possible opportunities for inclusion offered by the Ministry of Public Education (MEP). We used a qualitative research approach, and its study object was addressed using an explanatory-diagnostic design. The participants in this research included representatives of the various instances of the central offices of the MEP, responsible for political-administrative decision-making. Likewise, the necessary efforts were made to rescue the voice of the people closest to the real contexts where the educational processes are implemented. The study concludes that the educational modalities and programs appear as a proposal that lacks an analysis of suitability, relevance, or needs to which it responds. In addition, variables that condition its creation, as well as its evolution, are identified.